2012
DOI: 10.1021/jf300277g
|View full text |Cite
|
Sign up to set email alerts
|

Concord Grape Juice Supplementation and Neurocognitive Function in Human Aging

Abstract: Polyphenol compounds found in berry fruits, in particular flavonoids, have been associated with health benefits including improvement in cognition and neuronal function with aging. Concord grape juice contains polyphenols, including anthocyanins and flavanols, and previous research has shown improvement in a number of human health conditions with grape juice supplementation. In the current study, older adult subjects with mild cognitive impairment consumed Concord grape juice or placebo for 16 weeks and were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
195
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(206 citation statements)
references
References 45 publications
6
195
2
3
Order By: Relevance
“…The moderate and large effect sizes seen for the cognitive tasks highlight the clinical relevance of these cognitive improvements. These findings are consistent with those of recent human and animal studies showing improvement in cognitive performance in these domains with dietary supplementation with other anthocyanin-rich food sources (11)(12)(13)(31)(32)(33). Although, we have previously shown that intake of cherry juice does not impact acute cognition over 6h (34).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The moderate and large effect sizes seen for the cognitive tasks highlight the clinical relevance of these cognitive improvements. These findings are consistent with those of recent human and animal studies showing improvement in cognitive performance in these domains with dietary supplementation with other anthocyanin-rich food sources (11)(12)(13)(31)(32)(33). Although, we have previously shown that intake of cherry juice does not impact acute cognition over 6h (34).…”
Section: Discussionsupporting
confidence: 92%
“…Preliminary dietary supplementation studies have shown that blueberries (11) and concord grapes (12,13) improve aspects of memory in older adults over a 12 and 16 week intervention. Cherries, both the sweet and tart varieties, are a rich source of anthocyanins and to a lesser extent also contain flavan-3-ols and flavonols (14).…”
Section: Introductionmentioning
confidence: 99%
“…2 Grape juice has also been reported to improve cognitive and motor function. 3,4 Some of these effects are related to protection against oxidative stress, 5 and the antioxidant activity of grape juices may be an indicator of the relative level of health benefit they offer. Phenolic compounds are secondary plant metabolites that play a key role in the sensory and nutritional quality of fruits, vegetables and other plants.…”
Section: Introductionmentioning
confidence: 99%
“…8 Grape juices are rich in phenolic compounds and different studies have demonstrated that these substances possess biologi cal activity related to health benefits for the consumers. 9,10 The phenolic compounds in grape juices, mainly the flavonoids flavanols, flavonols and anthocyanins, are associated with improved health, along with other compounds which are not flavonoids, such as phenolic acids and the stilbene resveratrol. [11][12][13][14] The flavonols are represented mainly by kaempferol, quercetin and myricetin and simple orthomethylated derivatives such as isorhamnetin, which have received considerable interest due to their antioxidant properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation